"THE FREEDOM OF EXPRESSION AND OPINION IN UNITED STATES MASS MEDIA (STUDY CASE: JULIAN ASSANGE AND WIKILEAKS TOWARDS UNITED STATES DEMOCRACY)" - Muhammad Iwan Muharram (2012)

(untitled)
The objective of this undergraduate thesis is to explore more details about the freedom of expression and opinion in United States mass media with the case of Julian Assange and his website WikiLeaks towards United States democracy. This project purposes to know the reason why Julian Assange and WikiLeaks being a target hunt by United States government. We know that United States is democratic states which give freedom to speech, opinion and publish. Julian Assange is one of the worldwide journa